Communication Strategy of the Museum: Peculiarities of Formation by Means of PR Technologies - Butko, Larysa; Fedorenko, Svitlana; Lushakova, Alla (Socio-Cultural Management Journal, 2023)
Introduction. The transformation of the museum, the modernization of its activity as an object of the recreation industry in the context of cultural recreation, the transfer of knowledge in a new, interesting and accessible form caused the need to update traditional expositions, intensify exhibition activities and, as a result, change its communication policy. However, today in the theoretical and practical planes of socio-cultural management, the issues of its marketing communications remain unresolved, the main task of which is to help increase attendance, expand the museum audience, or spread information about the museum among those who are unable to directly familiarize themselves with its exposition. Purpose and methods. The purpose of the study is to determine the communication strategy of the regional museum on the example of the communal cultural institution “Kremenchuk Local History Museum” and to represent a series of communication events as a component of its PR activity. The purpose of the research is realized by performing the following tasks: determining the ideals, interests and values of the potential museum audience, as well as optimal communication channels; representation of developed PR activities aimed at establishing communication between the museum and visitors and promoting its popularization. Results. The article clarifies the results of a sociological survey conducted at the initial stage of the research in order to find out the direction of modeling special PR events for the promotion of the Kremenchuk Local History Museum and identifies a number of PR events aimed at establishing communication between the museum and visitors and promoting its popularization. Conclusions. The use of the latest marketing strategy paradigm together with the implementation of digital infrastructure will allow improving the processes of the museum management system, modernizing its main mechanisms, popularizing museum institutions and their services.